Alcohol consumption on pancreatic diseases - Herreros-Villanueva, Marta (Baishideng Publishing Group Co., Limited, 2013)
Although the association between alcohol and pancreatic diseases has been recognized for a long time, the impact of alcohol consumption on pancreatitis and pancreatic cancer (PC) remains poorly defined. Nowadays there is not consensus about the epidemiology and the beverage type, dose and duration of alcohol consumption causing these diseases. The objective of this study was to review the epidemiology described in the literature for pancreatic diseases as a consequence of alcoholic behavior trying to understand the association between dose, type and frequency of alcohol consumption and risk of pancreatitis and PC. The majority of the studies conclude that high alcohol intake was associated with a higher risk of pancreatitis (around 2.5%-3% between heavy drinkers and 1.3% between non drinkers). About 70% of pancreatitis are due to chronic heavy alcohol consumption. Although this incidence rate differs between countries, it is clear that the risk of developing pancreatitis increases with increasing doses of alcohol and the average of alcohol consumption vary since 80 to 150 g/d for 10-15 years. With regard to PC, the role of alcohol consumption remains less clear, and low to moderate alcohol consumption do not appear to be associated with PC risk, and only chronic heavy drinking increase the risk compared with lightly drinkers. In a population of 10%-15% of heavy drinkers, 2%-5% of all PC cases could be attributed to alcohol consumption. However, as only a minority (less than 10% for pancreatitis and 5% for PC) of heavily drinkers develops these pancreatic diseases, there are other predisposing factors besides alcohol involved. Genetic variability and environmental exposures such as smoking and diet modify the risk and should be considered for further investigations.